High-capacity soft carbon and preparation method and application thereof
By using medium and low sulfur oil slurry, ethylene tar, and reduced pressure residue as raw materials, blending and coking treatment, combined with pre-carbonization and carbonization treatment, the existing soft carbon anode materials are solved, and soft carbon preparation with high capacity and low cost is achieved, which is suitable for industrial production.
Patent Information
- Application Number
- CN202510116957.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-24
- Publication Date
- 2025-04-29
AI Technical Summary
The capacity of existing soft carbon anode materials is less than 260mAh/g, the first Coulomb efficiency is relatively low, the preparation process is complex, and the industrial production cost is high.
Medium- and low-sulfur oil slurry, ethylene tar and reduced pressure residue are used as raw materials, and high-capacity soft carbon is obtained by blending and coking treatment, and pre-carbonization and carbonization are carried out under an inert atmosphere to obtain high-capacity soft carbon.
The soft carbon capacity is ≥385mAh/g and the first Coulomb efficiency is ≥80%. The process is simple, the cost is low, and it is suitable for industrial production.
Smart Images

Figure CN119898756A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of soft carbon negative electrode material preparation, and in particular relates to high-capacity soft carbon and a preparation method and application thereof. Background Art
[0002] Due to the special structure of soft carbon negative electrode materials, they have excellent cycle performance, rate performance, safety performance, and their capacity can exceed the theoretical capacity. Soft carbon raw coke is mainly obtained through a series of treatments of petroleum coke, needle coke, carbon fiber, pitch coke, etc., but the capacity of the soft carbon negative electrode materials prepared at present is generally lower than 260mAh / g, and the first coulomb efficiency is low (<80%), so there is still a lot of room for development in the capacity of soft carbon materials.
[0003] In the prior art, Chinese patent CN101916856A discloses a negative electrode material for lithium-ion power and energy storage batteries and a preparation method thereof, which is obtained by carbonizing asphalt with a catalyst at 500 to 1300°C. The preparation method includes: increasing the temperature and pressure to cause a carbonization thermal polycondensation reaction, then washing, extracting, washing again, and drying to obtain an intermediate phase pellet precursor, which is then carbonized to obtain a negative electrode material for lithium-ion power and energy storage batteries. However, the capacity of the soft carbon product is relatively low (<300mAh / g). Chinese patent CN103050699A discloses a method for preparing a soft carbon negative electrode material for lithium ion batteries, comprising the following steps: mixing a catalyst with asphalt; heating to 180-380°C and reacting for at least 0.7 hours; heating to 320-600°C and reacting for at least 0.3 hours to obtain a mesophase spherical primary product; removing impurities from the mesophase spherical primary product and drying it to obtain a soft carbon-like carbon microsphere mesophase precursor; mixing the soft carbon-like carbon microsphere mesophase precursor with a nitrogen-containing compound and / or a boron-containing compound and standing; heating to 400-1600°C under a protective atmosphere, pyrolysis treatment for at least 0.6 hours to obtain a soft carbon negative electrode material. Although the invention material greatly improves the capacity of existing soft carbon materials, the preparation process is complicated and the cost of industrial production is high, which is not conducive to industrial production. Therefore, developing a high-capacity soft carbon with a simple production process and low cost is a technical problem in the field. Summary of the invention
[0004] The invention provides a high-capacity soft carbon and a preparation method and application thereof. The method provided by the invention is simple in process, and the prepared soft carbon has a capacity of ≥385 mAh / g and a first coulombic efficiency of ≥80%.
[0005] In order to achieve the above object, the present invention provides a method for preparing high-capacity soft carbon, comprising the following steps:
[0006] 1) blending medium-low sulfur oil slurry, ethylene tar, and vacuum residue to obtain a blended material; in the blended material, the proportion of asphaltene is 5-20%, the proportion of colloid is 10-30%, the proportion of aromatic fraction is 20-40%, and the proportion of saturated fraction is 10-30% by weight;
[0007] 2) coking the blended material under the protection of an inert atmosphere to obtain green coke for high-capacity soft carbon;
[0008] 3) The high-capacity soft carbon is subjected to pre-carbonization and carbonization treatment in sequence under the protection of an inert atmosphere to obtain high-capacity soft carbon.
[0009] Preferably, the sulfur content of the medium-low sulfur oil slurry in step 1) is 0.1% to 0.9% by weight.
[0010] Preferably, the sulfur content of the vacuum residue in step 1) is 0.1% to 0.9% by weight.
[0011] Preferably, the temperature during the coking treatment in step 2) is 400-500° C. and the time is 8-24 hours.
[0012] Preferably, the optical structure of the raw coke for high capacity soft carbon in step 2) is a state where a mosaic structure and a small domain structure coexist, wherein the small domain structure accounts for ≥30% and the mosaic structure accounts for ≥10%.
[0013] Preferably, the temperature of the pre-carbonization treatment in step 3) is 600-800° C. and the time is 1-3 hours.
[0014] Preferably, the temperature of the carbonization treatment in step 3) is 900-1200° C. and the time is 1-4 hours.
[0015] Preferably, step 3) further comprises crushing and screening the green coke for high-capacity soft carbon before the pre-carbonization treatment; the mesh size of the crushing and screening is 200 to 2000 meshes.
[0016] The present invention also provides a high-capacity soft carbon prepared by any one of the above methods, wherein the soft carbon has a performance capacity of ≥385 mAh / g and a first coulombic efficiency of ≥80%.
[0017] The present invention also provides the use of the high-capacity soft carbon described above in the negative electrode of a lithium battery.
[0018] Compared with the prior art, the advantages and positive effects of the present invention are:
[0019] (1) The present invention uses medium-low sulfur oil slurry, ethylene tar, and vacuum residue oil as raw materials to prepare green coke for high-capacity soft carbon. Using tar and residue oil as the main raw materials can control the fusion and growth of mesophase globules, making the mesophase tend to be complex, that is, transforming to a mosaic structure. The final coke structure will develop in a disordered direction, and after carbonization, there will be more active sites and spaces for storing lithium;
[0020] (2) Since the present invention introduces more small domains and mosaic structures at the raw material end, compared with high-oriented needle coke, there are more active sites and spaces for storing lithium after carbonization, and the capacity performance can reach more than 400 mAh / g;
[0021] (3) The preparation method of high-capacity soft carbon and raw materials provided by the present invention has simple process, high product yield, high product consistency and stability, and the preparation process of this method is green and pollution-free, low cost, and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a scanning electron microscope image of the raw coke prepared in Example 1;
[0023] Figure 2 This is the polarization image of the raw focus prepared in Example 1;
[0024] Figure 3 This is a scanning electron microscope image of the raw coke prepared in Example 2;
[0025] Figure 4 This is the polarization image of the raw focus prepared in Example 2;
[0026] Figure 5 This is a scanning electron microscope image of the raw coke prepared in Example 3;
[0027] Figure 6 This is the polarization image of the raw coke prepared in Example 3;
[0028] Figure 7 This is a scanning electron microscope image of the raw coke prepared in Example 4;
[0029] Figure 8 This is the polarization image of the raw coke prepared in Example 4;
[0030] Fig. 9 This is an electron microscope scanning image of the raw coke prepared in Comparative Example 1;
[0031] Fig.10 This is a scanning electron microscope image of the raw coke prepared in Comparative Example 2;
[0032] Fig.11 This is a scanning electron microscope image of the raw coke prepared in Comparative Example 3;
[0033] Fig.12 This is a scanning electron microscope image of the raw coke prepared in Comparative Example 4;
[0034] Fig.13 is a charge and discharge curve diagram of the soft carbon of Example 1;
[0035] Fig.14 is a charge and discharge curve diagram of the soft carbon of Example 2;
[0036] Fig.15 is a charge and discharge curve diagram of the soft carbon of Example 3;
[0037] Fig.16 This is the charge and discharge curve of the soft carbon of Example 4. DETAILED DESCRIPTION
[0038] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] The present invention provides a method for preparing high-capacity soft carbon, comprising the following steps:
[0040] 1) blending medium-low sulfur oil slurry, ethylene tar, and vacuum residue to obtain a blended material; in the blended material, the proportion of asphaltene is 5-20%, the proportion of colloid is 10-30%, the proportion of aromatic fraction is 20-40%, and the proportion of saturated fraction is 10-30% by weight;
[0041] 2) coking the blended material under the protection of an inert atmosphere to obtain green coke for high-capacity soft carbon;
[0042] 3) The high-capacity soft carbon is subjected to pre-carbonization and carbonization treatment in sequence under the protection of an inert atmosphere to obtain high-capacity soft carbon.
[0043] The present invention blends medium-low sulfur oil slurry, ethylene tar, and vacuum residue to obtain a blended material; by weight percentage, the asphaltene ratio in the blended material is 5-20%, the colloid ratio is 10-30%, the aromatic fraction ratio is 20-40%, and the saturated fraction ratio is 10-30%. In the present invention, by weight percentage, the sulfur content in the medium-low sulfur oil slurry is preferably 0.1%-0.9%; the sulfur content in the vacuum residue is preferably 0.1%-0.9%. In the present invention, filtering is preferably included before blending. In the present invention, the aperture of the filter screen for filtration is preferably 10-100 meshes. In the present invention, filtration can reduce the solid content, remove ash metal residues, and improve the oil slurry yield.
[0044] The present invention has no special limitation on the sources of the medium-low sulfur slurry oil, ethylene tar, and vacuum residue oil, and conventional products in the field can be used. The medium-low sulfur slurry oil, tar, and vacuum residue oil in the examples and comparative examples of the present invention are produced by Sinopec, Luqing Petrochemical, and Haike Ruilin Chemical Co., Ltd., respectively.
[0045] After obtaining the blended material, the present invention performs a coking treatment on the blended material under the protection of an inert atmosphere to obtain raw coke for high-capacity soft carbon. In the present invention, the temperature during the coking treatment is preferably 400-500°C, and the time is preferably 8-24h. In the present invention, the optical structure of the raw coke for high-capacity soft carbon is a state in which a mosaic structure and a small domain structure coexist, wherein the small domain structure accounts for ≥30% and the mosaic structure accounts for ≥10%. In the present invention, the mosaic structure refers to a same-color area size ≤10μm in a polarized image, and the small domain structure refers to a same-color area size between 10 and 30μm in a polarized image.
[0046] After obtaining the green coke for high-capacity soft carbon, the present invention sequentially performs pre-carbonization and carbonization treatment on the green coke for high-capacity soft carbon under the protection of an inert atmosphere to obtain high-capacity soft carbon. In the present invention, before the pre-carbonization treatment, it is preferred to also include crushing and screening the green coke for high-capacity soft carbon; the mesh number of the crushing and screening is preferably 200-2000 mesh. In the present invention, the particle size can be controlled in advance by crushing and screening the green coke, and the uniformity of the particle reaction is improved during the subsequent pre-carbonization and carbonization process, and the integrity of the particles is also avoided from being destroyed after the sample is crushed after carbonization. In the present invention, the temperature of the pre-carbonization treatment is preferably 600-800°C, and the time is preferably 1-3h; the temperature during the carbonization treatment is preferably 900-1200°C, and the time is preferably 1-4h. In the present invention, pre-carbonization is first performed at 600-800°C, and then the temperature is raised to 900-1200°C for carbonization, which can provide sufficient reaction time for the development of microcrystals.
[0047] The present invention also provides a high-capacity soft carbon prepared by any one of the above methods, wherein the soft carbon has a performance capacity of ≥385 mAh / g and a first coulombic efficiency of ≥80%.
[0048] The present invention also provides the use of the high-capacity soft carbon described above in the negative electrode of a lithium battery.
[0049] The present invention uses medium- and low-sulfur oil slurry, tar, and vacuum residue oil as raw materials to prepare high-capacity soft carbon raw coke. Ethylene tar contains more easily condensed alkenyl aromatics and has a fast condensation rate, and can be used as the nucleus for the development of mesophase globules; the high saturation content in the residue oil component plays a role in maintaining the reaction activity of the system and the low viscosity state of the system. Using tar and residue oil as the main raw materials can control the fusion and growth of the mesophase globules, and the mesophase will tend to be complex, that is, transformed into a mosaic structure, and its final coke structure will develop in a disordered direction. Since the present invention introduces more small domains and mosaic structures at the raw material end, compared with highly oriented needle coke, there are more active sites and spaces for storing lithium after carbonization, and the capacity is above 400mAh / g.
[0050] The invention uses medium- and low-sulfur oil slurry, tar and vacuum residue oil as raw materials, filters them and directly performs coking in a heating furnace under temperature and time control, obtains a raw coke sample, and then crushes and screens it and performs pre-carbonization and carbonization in an atmosphere furnace under temperature and time control. The process is simple and feasible, the product yield is high, and the product consistency and stability are high. In addition, the preparation process of the method is green and pollution-free, the cost is low, and the method is suitable for industrial production.
[0051] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0052] Example 1
[0053] Filter medium-low sulfur oil slurry (sulfur content of 0.8%), ethylene tar, and vacuum residue oil (sulfur content of 0.4%) separately. After filtration, blend medium-low sulfur oil slurry (sulfur content of 0.8%), ethylene tar, and vacuum residue oil (sulfur content of 0.4%) in a mass ratio of 1:1:1. The proportion of asphaltene in the blended materials is 15%, the proportion of gum is 25%, the proportion of aromatic components is 35%, and the proportion of saturated components is 25%. The raw materials are coked under an inert atmosphere. The coking temperature is controlled at 480°C and the coking time is 12 hours. After the coking is completed, green coke is obtained. The prepared green coke product was subjected to electron microscope scanning and polarization testing. The specific results are as follows: Figure 1 and 2 As shown. Figure 1 and 2 It can be seen that the prepared focal orientation is poor, the structure is compact, and there are a large number of wrinkles and mosaic structures.
[0054] The obtained green coke was crushed and sieved to a particle size of 10 microns (D50), calcined at 800℃ in a nitrogen atmosphere for 2 hours, and then heated to 1000℃ in a nitrogen furnace for 2 hours to obtain high-capacity soft carbon. The charge and discharge curve of the soft carbon is shown in the figure. Fig.13 shown.
[0055] Example 2
[0056] Filter medium and low sulfur oil slurry (sulfur content of 0.5%), ethylene tar and vacuum residue oil (sulfur content of 0.5%) separately. After filtration, blend medium and low sulfur oil slurry (sulfur content of 0.5%), ethylene tar and vacuum residue oil (sulfur content of 0.5%) in a mass ratio of 3:2:1. The asphaltene ratio, colloid ratio, aromatic fraction ratio and saturated fraction ratio are 12%, 27%, 40% and 21% in the blended materials. The raw materials are coked under an inert atmosphere. The coking temperature is controlled at 460°C and the coking time is 24h. Green coke is obtained after the coking is completed. The prepared product was subjected to electron microscope scanning and polarization test. The specific results are as follows: Figure 3 and 4 As shown. Figure 3 and 4 It can be seen that the prepared focal orientation is poor, with more lamellar structures.
[0057] The obtained green coke was crushed and sieved to a particle size of 10 microns (D50), calcined at 600℃ in a nitrogen atmosphere for 3 hours, and then heated to 1200℃ in a nitrogen furnace for 1 hour to obtain high-capacity soft carbon. The charge and discharge curve of the soft carbon is shown in the figure. Fig.14 shown.
[0058] Example 3
[0059] Filter the medium and low sulfur oil slurry, ethylene tar and vacuum residue oil separately. After filtering, blend the medium and low sulfur oil slurry (sulfur content of 0.7%), ethylene tar and vacuum residue oil (sulfur content of 0.6%) in a mass ratio of 3:3:4. The asphaltene ratio, colloid ratio, aromatic fraction ratio and saturated fraction ratio in the blended materials are 13%, 30%, 37% and 20%. The raw materials are coked in an inert atmosphere. The coking temperature is controlled at 500°C and the coking time is 8 hours. Green coke is obtained after the coking is completed. The prepared product was subjected to electron microscope scanning and polarization testing. The specific results are as follows: Figure 5 and 6 As shown. Figure 5 and 6 It can be seen that the prepared coke has a dense structure, a large number of wrinkles, and an obvious mosaic structure.
[0060] The obtained green coke was crushed and sieved to a particle size of 10 microns (D50), calcined at 800℃ in a nitrogen atmosphere for 2 hours, and then heated to 900℃ in a nitrogen furnace for 4 hours to obtain high-capacity soft carbon. The charge and discharge curve of the soft carbon is shown in the figure. Fig.15 shown.
[0061] Example 4
[0062] Filter the medium and low sulfur oil slurry, ethylene tar and vacuum residue oil separately. After filtering, blend the medium and low sulfur oil slurry (sulfur content of 0.8%), ethylene tar and vacuum residue oil (sulfur content of 0.4%) in a mass ratio of 2:1:3. The asphaltene ratio, colloid ratio, aromatic fraction ratio and saturated fraction ratio are 11%, 29%, 36% and 24% in the blended materials. The raw materials are coked in an inert atmosphere. The coking temperature is controlled at 500°C and the coking time is 12h. Green coke is obtained after the coking is completed. The prepared product was subjected to electron microscope scanning and polarization testing. The specific results are as follows: Figure 7 and 8 As shown. Figure 7 and 8 It can be seen that the prepared focal orientation is poor, the structure is compact, and the content of small platelets is high.
[0063] The obtained green coke was crushed and sieved to a particle size of 10 microns (D50), calcined at 800℃ in a nitrogen atmosphere for 2 hours, and then heated to 1000℃ in a nitrogen furnace for 2 hours to obtain high-capacity soft carbon. The charge and discharge curve of the soft carbon is shown in the figure. Fig.16 shown.
[0064] Comparative Example 1
[0065] The difference from Example 3 is that the raw material is only medium-low sulfur slurry oil, and ethylene tar and vacuum residue oil are not added. The specific operation is as follows:
[0066] The medium-low sulfur oil slurry (sulfur content of 0.7%) was filtered. After filtration, the medium-low sulfur oil slurry (sulfur content of 0.7%) was passed into an inert atmosphere for coking treatment. The coking temperature was controlled at 500°C and the coking time was 8 hours. After the coking was completed, green coke was obtained. The prepared product was tested by electron microscopy. The specific results are as follows: Fig. 9 As shown. Fig. 9 It can be seen that the prepared green coke has a dense structure and a more obvious layered structure.
[0067] The obtained green coke was crushed and sieved to a particle size of 10 microns (D50), calcined at 800°C in a nitrogen atmosphere for 2 hours, and then the nitrogen furnace was heated to 900°C for 4 hours to obtain soft carbon.
[0068] Comparative Example 2
[0069] The difference from Example 2 is that the raw material is only vacuum residue oil, and ethylene tar and medium-low sulfur oil slurry are not added. The specific operation is as follows:
[0070] The vacuum residue oil (sulfur content of 0.5%) was filtered. After filtering, the vacuum residue oil (sulfur content of 0.5%) raw material was passed into an inert atmosphere for coking treatment. The coking temperature was controlled at 460°C and the coking time was 24 hours. After the coking was completed, green coke was obtained. The prepared product was tested by electron microscopy. The specific results are as follows Fig.10 As shown. Fig.10 It can be seen that the prepared comparative focus 2 has a dense structure and a more obvious layered structure.
[0071] The obtained green coke was crushed and sieved to a particle size of 10 microns (D50), calcined at 600°C in a nitrogen atmosphere for 3 hours, and then the nitrogen furnace was heated to 1200°C for 1 hour to obtain soft carbon.
[0072] Comparative Example 3
[0073] The difference from Example 1 is that the raw material is only ethylene tar, and no vacuum residue oil and medium-low sulfur slurry are added. The specific operation is as follows:
[0074] The ethylene tar was filtered. After filtering, the ethylene tar was passed into an inert atmosphere for coking treatment. The coking temperature was controlled at 480°C and the coking time was 12 hours. After the coking was completed, green coke was obtained. The prepared green coke product was tested by electron microscopy. The specific results are as follows: Fig.11 As shown. Fig.11 It can be seen that the prepared green coke has a dense structure and a more obvious layered structure.
[0075] The obtained raw coke was crushed and sieved to a particle size of 10 microns (D50), calcined at 800°C in a nitrogen atmosphere for 2 hours, and then the nitrogen furnace was heated to 1000°C for 2 hours to obtain soft carbon.
[0076] Comparative Example 4
[0077] Filter the medium-low sulfur oil slurry (sulfur content of 0.7%) and vacuum residue oil (sulfur content of 0.5%). After filtration, blend the medium-low sulfur oil slurry (sulfur content of 0.7%) and vacuum residue oil (sulfur content of 0.5%) in a mass ratio of 1:1. The asphaltene ratio, colloid ratio, aromatic fraction ratio and saturated fraction ratio are 27%, 30%, 15% and 28% in the blended materials. The raw materials are coked under an inert atmosphere. The coking temperature is controlled at 480°C and the coking time is 12 hours. Green coke is obtained after the coking is completed. The prepared product is tested by electron microscopy. The specific results are as follows: Fig.12 As shown. Fig.12 It can be seen that the prepared green coke has a dense structure and a more obvious layered structure.
[0078] The obtained raw coke was crushed and sieved to a particle size of 10 microns (D50), calcined at 800°C in a nitrogen atmosphere for 2 hours, and then the nitrogen furnace was heated to 1000°C for 2 hours to obtain soft carbon.
[0079] Performance Testing
[0080] The performance tests were performed on the soft carbon prepared in the examples and comparative examples. The specific operations are as follows:
[0081] The obtained high-capacity soft carbon, binder and carbon black were fully mixed in a mass ratio of 94.5:4:1.5, and N-methylpyrrolidone (NMP) was added to prepare the negative electrode slurry, which was then evenly coated on the copper foil, dried, and rolled into a circular electrode sheet with a diameter of 14 mm. The electrode sheet was vacuum dried at 110°C for 12 hours, and then the battery was assembled in a glove box filled with argon, with metallic lithium as the counter electrode.
[0082] The charge and discharge capacity test was carried out on the Land battery test system. The charge and discharge voltage range was 0.005V to 2V, and the current density was 35mA / g. The specific charge and discharge performance is shown in Table 1.
[0083] Table 1
[0084]
[0085] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing high-capacity soft carbon, characterized in that: The steps include: 1) blending medium-low sulfur oil slurry, ethylene tar, and vacuum residue to obtain a blended material; in the blended material, the proportion of asphaltene is 5-20%, the proportion of colloid is 10-30%, the proportion of aromatic fraction is 20-40%, and the proportion of saturated fraction is 10-30% by weight; 2) coking the blended material under the protection of an inert atmosphere to obtain green coke for high-capacity soft carbon; 3) The high-capacity soft carbon is subjected to pre-carbonization and carbonization treatment in sequence under the protection of an inert atmosphere to obtain high-capacity soft carbon.
2. The preparation method according to claim 1, characterized in that: Calculated by weight percentage, the sulfur content in the medium-low sulfur oil slurry in step 1) is 0.1% to 0.9%.
3. The preparation method according to claim 1, characterized in that: In terms of weight percentage, the sulfur content of the vacuum residue in step 1) is 0.1% to 0.9%.
4. The preparation method according to claim 1, characterized in that: The temperature of the coking treatment in step 2) is 400-500° C. and the time is 8-24 hours.
5. The preparation method according to claim 1, characterized in that: The optical structure of the raw coke for high capacity soft carbon in step 2) is a state where a mosaic structure and a small domain structure coexist, wherein the small domain structure accounts for ≥30% and the mosaic structure accounts for ≥10%.
6. The preparation method according to claim 1, characterized in that: The temperature of the pre-carbonization treatment in step 3) is 600-800°C and the time is 1-3h.
7. The preparation method according to claim 1, characterized in that: The temperature of the carbonization treatment in step 3) is 900-1200° C. and the time is 1-4 hours.
8. The preparation method according to claim 1, characterized in that: Step 3) also includes crushing and screening the green coke for high-capacity soft carbon before pre-carbonization treatment; the mesh size of the crushing and screening is 200 to 2000 meshes.
9. The high capacity soft carbon prepared by the method of any one of claims 1 to 8, characterized in that: The soft carbon has a performance capacity of ≥385 mAh / g and a first coulombic efficiency of ≥80%.
10. Use of the high-capacity soft carbon according to claim 9 in the negative electrode of a lithium battery.
Citation Information
Patent Citations
Cathode material for lithium-ion power and energy storage battery and preparation method thereof
CN101916856A
Soft carbon negative electrode material of lithium ion battery and preparation method thereof
CN103050699A